Thymidine phosphorylase in cancer aggressiveness and chemoresistance. (June 2018) - Furukawa, Tatsuhiko; Tabata, Sho; Yamamoto, Masatatsu; Kawahara, Kohichi; Shinsato, Yoshinari; Minami, Kentaro; Shimokawa, Michiko; Akiyama, Shin-ichi
Graphical abstract: Abstract: Thymidine phosphorylase (TP) is a rate-limiting enzyme in thymidine catabolism. TP has several important roles in biological and pharmacological mechanisms; importantly TP acts as an angiogenic factor and one of metabolic enzymes of fluoro-pyrimidine anticancer agents and modifies inflammation. Improving our understanding of the characteristics and functions of TP has led to the development of novel TP-based anticancer therapies. We recently reported that TP-dependent thymidine catabolism contributes to tumour survival in low nutrient conditions and the pathway from thymidine to the glycolysis cascade is affected in the context of physiological and metabolic conditions. In this review, we describe recent advancement in our understanding of TP, with a focus on cancer cell biology and the pharmacology of pyrimidine analogue anticancer agents. This review provides comprehensive understanding of the molecular mechanism of TP function in cancer.